(untitled) (Global Journal of Medical Research, 2020)
Open restaurant food vendor and consumer status as well as hygienic condition of different types of food at Dumki, Patuakhali upazila, and Kuakata union of Patuakhali district were determined. Ninety shops with 180 open restaurant food samples were collected. Among the food vendors, 97.78% were male. Maximum (68%) of them were between 21-40 years of age. The majority (54%) of them were primary educated. Half of the vending shops located on the sidewalk and one third on the footpath. The majority (81%) of the respondent had their daily net profit up to TK. 500. About 64% of vendors did not cover their food while selling; 47.78% used unclean towels and 27.78 % used plate followed by paper & polythene (49.45%) as a serving media. Everyone used tube-well water as drinking water. The few had a business permit or food-selling permit. Maximum (83.33%) consumers were male, and the highest consumers (76.667%) were aged between 21-40 years. The majority (57.77%) of consumers always consume foods on roadside. 60% of the consumers suffered from diseases. Only 4.44% of consumer had enough knowledge about nutrition and 8.89% in hygiene.